Sports Coaching and Koni Bali's Leading Sports - I Putu Darmayasa; Suratmin Suratmin (UNIB Press, 2023)
Sports development implemented by KONI Bali through sports coaching management, sports coaching, coaching model development, training programs, training targets, and evaluation of KONI Bali sports , coaching, become thoughts, concentrations, and coaching strategies. Sports Development to get superior athletes is done with long-term programs and continuous coaching. Sports development is an important element to develop the talents and potential of athletes and to obtain optimal achievements both regionally, nationally, and internationally. It is proven that KONI Bali will be ranked 5th (five) in PON Papua in 2022, so it is necessary to establish superior sports to achieve national and international achievements. The purpose of the study was to examine the coaching of sports and superior sports of KONI Bali. This study uses a survey method to obtain descriptive sports coaching data and KONI Bali's leading sports. The research sample is the management of KONI Bali in 2022. Data was obtained by interviews with KONI administrators, questionnaires, and archives/documents of sports results/achievements. The data analysis used is data triangulation.The conclusions of the study are (1) the target of KONI Bali province by effectuating sports coaching strategies with priority on individual sports, so that coaching is carried out with focus and professionalism, and (2) determining the leading sports of Bali province, especially superior sports coaching with centralization and decentralization on an ongoing basis.